2023
DOI: 10.1002/vms3.1145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uterine torsion intrapartum on concentrations of placental estrogens and progesterone in cattle

Abstract: Objective The current study investigates how uterine torsion influences placental oestrogens and progesterone blood concentrations in intrapartum cows. Our research tests the hypothesis that intrapartum uterine torsion impairs the ability of the placenta to synthesize steroids and may also suppress the release of synthesized steroids into the maternal circulation. Methods The study included a total number of 37 intrapartum dairy cows of various breeds and ages. These animals were transported to our clinic by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…One possible explanation is that not only P4 but also cross-reacting inactive P4 of P4 effects in prepartal cows is not only based on a stop of P4 production but also on its conversion into inactive metabolites in certain tissues and that IDC is associated with impaired steroid metabolism after all. Interestingly, in a previous study, a significant positive correlation between P4 and FTE was also observed in eutocic cows, but not in animals with uterine torsion (Sendag et al, 2023).…”
Section: Discussionmentioning
confidence: 65%
“…One possible explanation is that not only P4 but also cross-reacting inactive P4 of P4 effects in prepartal cows is not only based on a stop of P4 production but also on its conversion into inactive metabolites in certain tissues and that IDC is associated with impaired steroid metabolism after all. Interestingly, in a previous study, a significant positive correlation between P4 and FTE was also observed in eutocic cows, but not in animals with uterine torsion (Sendag et al, 2023).…”
Section: Discussionmentioning
confidence: 65%